2013
DOI: 10.1088/1748-6041/8/4/045010
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of a weakly denatured collagen fiber scaffold with excellent biocompatibility and space maintenance ability

Abstract: Although collagen scaffolds have been used for regenerative medicine, they have insufficient mechanical strength. We made a weakly denatured collagen fiber scaffold from a collagen fiber suspension (physiological pH 7.4) through a process of freeze drying and denaturation with heat under low pressure (1 × 10(-1) Pa). Heat treatment formed cross-links between the collagen fibers, providing the scaffold with sufficient mechanical strength to maintain the space for tissue regeneration in vivo. The scaffold was em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…In other words, even if a scaffold is physically hard, it will be considered to have poor durability if it has to be removed early owing to a strong foreign body reaction in vivo . Previously, it was shown that a collagen scaffold with durability, biocompatibility, and superior cell infiltration ability could be manufactured by pouring the collagen fiber suspension at a physiological pH of 7.4 into a container that provides orientation to the collagen fibers, followed by freezing at −10°C, drying completely, and treating the fibers at 140°C for 6 h under low pressure (1 × 10 −1 Pa) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In other words, even if a scaffold is physically hard, it will be considered to have poor durability if it has to be removed early owing to a strong foreign body reaction in vivo . Previously, it was shown that a collagen scaffold with durability, biocompatibility, and superior cell infiltration ability could be manufactured by pouring the collagen fiber suspension at a physiological pH of 7.4 into a container that provides orientation to the collagen fibers, followed by freezing at −10°C, drying completely, and treating the fibers at 140°C for 6 h under low pressure (1 × 10 −1 Pa) …”
Section: Discussionmentioning
confidence: 99%
“…Scaffolds were fabricated as described previously . In brief, atelocollagen (NMP collagen PS, provided by Nippon Meatpackers, Ibaraki, Japan) was used to make the collagen scaffold.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 However, the use of collagen-based scaffolds is hampered by the insufficient mechanical properties of these materials. 23 To tackle these conflicting demands, we have chosen the CGP copolymer combining high mechanical properties and suitability for electrospinning of polylactide 9,24 with biocompatibility, high cell adhesion capacity and antibacterial properties of chitosan. 23 To tackle these conflicting demands, we have chosen the CGP copolymer combining high mechanical properties and suitability for electrospinning of polylactide 9,24 with biocompatibility, high cell adhesion capacity and antibacterial properties of chitosan.…”
Section: Bilayered Cgp Scaffold Developmentmentioning
confidence: 99%